Unearthed opium: development of a UHPLC-MS/MS method for the determination of Papaver somniferum alkaloids in Daunian vessels - Vincenti, Flaminia; Montesano, Camilla; Ciccola, Alessandro; Serafini, Ilaria; Favero, Gabriele; Pallotta, Matteo; Pagano, Flavia; Di Francesco, Gaia; Croce, Martina; Leone, Maria Laura; Muntoni, Italo Maria; Sergi, Manuel (Frontiers in Chemistry, 2023)
Organic residue The analysis of organic residue in ancient vessels, to investigate early age civilizations habits, is an important archaeological application that needs advanced analytical methods. However, these procedures should , meeting inherent requisites such as low sampling invasiveness and high sensitivity for trace analysis. This paper deals with the development of advanced analytical methods for the detection of opium alkaloids in ceramic vessels and its first application to the study of Daunian pots dating back to the VIII-IV sec B.C. All the stages of the analytical procedure from sampling to analysis were carefully optimized. Concerning sampling, the traditional scraping approach was compared with a swabbing strategy which permitted to minimize sample encroachment. Extraction was based on pressurized liquid extraction (PLE) or ultrasound assisted liquid extraction followed by dispersive liquid liquid extraction (dLLME), which allowed concentration enrichment. On the other hand, a UHPLC-MS/MS method was specifically developed and validated in order to obtain reliable data. Some Daunians pots, belonging to the Ceci-Macrini private archaeological collection, were selected for sample withdrawal as their iconography could suggest opium usage.Different samples from 14 Daunians pots, whose iconography could suggest opium usage; and belonging to the Ceci-Macrini private archaeological collection were analyzed with the described methods.Several of the analyzed samples tested resulted positive to thebaine and less frequently to morphine and codeine; in detail, 70% of the analyzed items, tested positive for at least an opium alkaloid. Positive findings were common to all the samples collected in the pots, suggesting that scraping and 2 This is a provisional file, not the final typeset article swabbing provided comparable results and validating this unusual sampling strategy. All samples were additionally analyzed by UHPLC-HRMS to further improve the confidence level of the identified compounds. The obtained results shed new light on the hypothesis of opium the usagee of Opium by the ancient Daunian civilization. Furthermore, this study provided suitable analytical tools for further investigations on the same topic, with a good level of confidence in the quality of the results.